Management of Nutrient Interactions in Agriculture/ (Acc: 887) - Tandon, H. L. S. (Hari Lal Singh), 1943-; Fertiliser Development and Consultation Organisation (New Delhi, India : Fertiliser Development and Consultation Organisation, 1992)
Eight articles on balanced and efficient use of fertilizers.
Keywords: Crops; Fertilizers; Crops and soils